Dogs can detect scat samples more efficiently than humans: an experiment in a continuous Atlantic Forest remnant - Oliveira, Márcio L. de [UNESP]; Norris, Darren [UNESP]; Ramírez, José F. M. [UNESP]; Peres, Pedro H. de F. [UNESP]; Galetti, Mauro [UNESP]; Duarte, José M. B. [UNESP] (Sociedade Brasileira de Zoologia, 2012)
Scat-detection dogs have been used to locate feces of rare and elusive species across tropical biomes. However their detection efficiency in relation to human observers has rarely been evaluated. In this study, we evaluated the ability of a scat detection dog to locate feces in comparison with human researchers. Human researchers and a scat detection dog surveyed for deer (Mazama spp.) feces in dense ombrofilous Atlantic forest in the Paranapiacaba continuum, SP, Brazil. A controlled experiment was used to assess the maximum effective perpendicular distance from a transect search line that the dog could detect a Mazama spp fecal sample. Results from a linear regression model revealed that the maximum effective perpendicular distance from a transect search line that the dog could detect a scat was 7.2 m. The detection success from our surveys in the Atlantic forest was zero for humans and 0.15 samples/ha or 0.20 samples/km walked for the dog team. Our results demonstrated the importance of scat-detection dogs for non invasive sampling and provide data relevant for the design of future studies.
Keywords: Deer; fecal samples; Mazama; sampling